[2](1, 3)Adamantano[2](2, 7)pyrenophane: A Hydrocarbon with a Large Dipole Moment. Issue 32 (1st July 2016) - Kahl, Paul; Wagner, J. Philipp; Balestrieri, Ciro; Becker, Jonathan; Hausmann, Heike; Bodwell, Graham J.; Schreiner, Peter R.
Abstract: The fusion of the sp 3 ‐hybridized parent diamondoid adamantane with the sp 2 ‐hybridized pyrene results in a hybrid structure with a very large dipole moment which arises from bending the pyrene moiety. Presented herein is the synthesis, study of the electronic and optical properties, as well as the dynamic behavior of this new hydrocarbon. Abstract : Diamond in the rough : Molecular electronics with single hydrocarbons may be possible by combining the sp 3 ‐hybridized diamond with sp 2 ‐hybridized graphene carbon allotropes. This combination is mimicked through the combination of a diamondoid with pyrene as a graphene model. The nonpolar components lead to a new, highly strained hydrocarbon with a very large and optimally positioned dipole moment needed for molecular rectification.